Comparison of ALE, LBE and pressure time history methods to evaluate extreme loading effects in RC column. (December 2020) - Abedini, M.; Zhang, Chunwei; Mehrmashhadi, J.; Akhlaghi, E.
Abstract: There is an urgent need to develop appropriate techniques that will enable structural engineers to design and assess building structures which are vulnerable to blast events to protect lives and public property. In the current research, a complete procedure is performed to select the appropriate blast loading techniques for RC columns under detonation events. Therefore, three finite element techniques of Arbitrary Lagrangian Eulerian (ALE), Load Blast Enhanced (LBE), and pressure-time history methods (referred to as simplified method) are evaluated to simulate blast loads in RC columns based on the LS-DYNA platform. The three approaches are validated against experimental test results, and outcomes are in great concurrence with test data. According to the results, the measured deflection of the middle height in the experiment is 12.5 mm whereas numerical analysis using ALE, LBE and simplified methods resulted in 12 mm, 13.83 mm and 11.96 mm respectively. Therefore, the relative error for ALE, LBE and simplified methods are 4.16%, 9.61%, and 4.51%, respectively. The residual deflection computed for ALE, LBE and simplified methods are 6.4 mm, 5.49 mm, and 6.52 mm, respectively while the residual displacement in the experimental test is 6.3 mm. The relative errors are 1.56%, 14.75% and 3.37% for ALE, LBE, and simplified methods. The findings show that the LBE and simplified methods are sufficient to predict blast load. If a rapid analysis is required, LBE and simplified methods are more suitable. However, if actual blast pressure is significant to consider, then ALE is the best approach because it can simulate the propagation of shock waves. Also in this study, dynamic response of RC columns under blast detonations is presented that the results of the numerical study show that the scaled distance, charge weight and standoff distance has a significant effect on the behavior of RC columns under explosion loading. The outcome of this study benefits the knowledge of structural responses to blast loads and improves finite element (FE) models to assess concrete structures performance against extreme loads.